The core role of central nervous system in sepsis-related organ damage - Tang, Fajuan; Wu, ShanShan; Zou, Zhuan; Li, Xihong; Qiao, Lina (Frontiers in Immunology, 2025)
Sepsis-induced multiple organ dysfunction syndrome is the leading cause of mortality among patients with sepsis. Its pathophysiological mechanisms encompass various factors, including dysregulated inflammatory responses, endothelial injury and microcirculatory disturbances, abnormal activation of cell death pathways, as well as metabolic reprogramming and immune interactions. The central nervous system (CNS) is one of the earliest and most susceptible organs affected during the septic process. This involvement not only results in brain dysfunction due to neuronal damage, excessive activation of microglia, and neuroinflammatory responses but also contributes to systemic organ damage through diverse neural regulatory mechanisms. Specifically, the CNS influences the function of distant organs via the autonomic nervous system—comprising inhibition of the vagus nerve cholinergic anti-inflammatory pathway and excessive activation of sympathetic nerve pathways—the neuroimmune regulatory network, central trained immunity regulation, extravasation of brain-derived inflammatory factors, and exosome transport. This paper provides a systematic review of key pathogenic mechanisms underlying sepsis-related organ damage while emphasizing the pivotal regulatory role played by the central nervous system in this pathological process along with its potential therapeutic implications.